2008
DOI: 10.4049/jimmunol.180.4.2099
|View full text |Cite
|
Sign up to set email alerts
|

Preassociation of IL-15 with IL-15Rα-IgG1-Fc Enhances Its Activity on Proliferation of NK and CD8+/CD44high T Cells and Its Antitumor Action

Abstract: In the induction of an immune response, IL-15Rα on APCs transpresents IL-15 to NK and CD8+/CD44high T cells that express the IL-2/15Rβ and γc subunits only. In this study, we show data mimicking this transpresentation by using IL-15 preassociated with a chimeric protein that is comprised of the extracellular domain of murine IL-15Rα and the Fc portion of human IgG1. When tested in vitro, IL-15Rα-IgG1-Fc strongly increased the IL-15-mediated proliferation of murine NK and CD8+/CD44high T cells. The effect of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
169
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 31 publications
11
169
0
Order By: Relevance
“…Treatment of mice with IL-15xIL15RaFc complexes enhanced the proliferation of CD8 þ memory T cells and NK cells in vivo. Furthermore, tumor burden could be reduced and survival extended in a systemic B16 melanoma mouse model (24,25). Similar results were obtained by an IL-15/IL-15Ra domain fusion protein (26,27).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Treatment of mice with IL-15xIL15RaFc complexes enhanced the proliferation of CD8 þ memory T cells and NK cells in vivo. Furthermore, tumor burden could be reduced and survival extended in a systemic B16 melanoma mouse model (24,25). Similar results were obtained by an IL-15/IL-15Ra domain fusion protein (26,27).…”
Section: Introductionsupporting
confidence: 71%
“…Binding of soluble IL-15Ra to soluble IL-15 led to competition with cell surface receptors inhibiting IL-15-mediated function (14). Later, complex formation of recombinant soluble IL-15 and IL-15Ra-Fc molecules was reported to enhance the bioactivity of IL-15, inducing proliferation of NK cells and memory T cells in vitro and in vivo (23,25). Structural studies identified the "sushi" region in the IL-15Ra as the main responsible element for IL-15 binding (31).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Attempts to treat tumor models in mice by administration of IL-15 have proven effective. [28][29][30][31][32][33][34][35] Whereas wild-type C57Bl/6 mice died by 40 days after IV injection of MC38 colon carcinoma cells, IL-15 transgenic mice did not develop metastases and survived. 28 Furthermore, therapy with IL-15 prolonged survival of mice that received syngeneic CT26, MC38 colon carcinoma cells, or B16 melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…28 Furthermore, therapy with IL-15 prolonged survival of mice that received syngeneic CT26, MC38 colon carcinoma cells, or B16 melanoma cells. 28,33 Klebanoff et al demonstrated that IL-15 enhanced the in vivo activity of tumor-reactive CD8 ϩ T cells in the T-cell receptortransgenic mouse (Pmel-1), in which CD8 T cells recognize an epitope derived from the melanoma antigen GP100. 31 In other studies, synergy between IL-21 and IL-15 in regulating CD8 ϩ T-cell expansion and function yielded cures of established large B16 melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the complex of IL-15Rα and IL-15 is a strong stimulator for the responses of NK cells and CD8 + T cells (Dubois et al, 2008;Epardaud et al, 2008;Han et al, 2011). We prepared IL-15R/IL-15 fusion protein by fusing IL-15 receptor α sushi domain with IL-15 (Mortier et al, 2006).…”
Section: Resultsmentioning
confidence: 99%